World Public Sector Report 2019 - United Nations (United Nations, 2019)
The 2030 Agenda and the Sustainable Development Goals (SDGs) prominently feature institutions, both as a cross-cutting issue in many of the goals and as a standalone goal (SDG 16). The World Public Sector Report 2019 looks at national-level developments in relation to several concepts highlighted in the targets of Goal 16, which are viewed as institutional principles: access to information, transparency, accountability, anti-corruption, inclusiveness of decision-making processes, and non-discrimination. The report surveys global trends in these areas, documenting both the availability of information on those trends and the status of knowledge about the effectiveness of related policies and institutional arrangements in different national contexts. It also demonstrates how the institutional principles of SDG 16 have been informing the development of institutions in various areas, including gender equality and women’s empowerment (SDG 5). The report further examines two critical instruments that can support effective public institutions and public administration for the SDGs, namely national budget processes and risk management. The World Public Sector Report 2019 aims to inform the first review of SDG 16 at the United Nations high-level political forum on sustainable development in July 2019, and to contribute to future efforts to monitor progress on SDG 16. By reviewing key challenges and opportunities for public institutions in the context of the implementation of the 2030 Agenda at the national level, the report also aims to inform efforts by all countries to create effective institutions to deliver the Sustainable Development Goals.